CASE BASED REASONING UNTUK MENDIAGNOSA PENYAKIT GIGI DAN MULUT MENGGUNAKAN METODE BLOCK CITY - Emanuel Fahik; Derwin R Sina; Arfan Y Mauko (J-Icon : Jurnal Komputer dan Informatika, 2017)
Case Based Reasoning (CBR) method is one method to build a system with new case decision based on solution from previous cases by calculating similarity level. In this study, the authors apply CBR to diagnose dental and mouth disease in humans. Sources of system knowledge are obtained by collecting cases that have occurred before. The calculation of similarity values ​​using the Block City Gower method with threshold 60%. This system can diagnose 5 diseases based on 26 existing symptoms. The output of the system in the form of the illness experienced by the patient based on the symptoms entered by non-physician medical personnel, as well as the treatment solution which accompanied the presentation of similarities with the previous case to show the truth level of possible diagnosis. Based on the results of the test case obtained the results: the system can take back the old case is appropriate and has used the formulation of Block City method correctly indicated with 100% accuracy, and use 122 cases is optimal enough to diagnose 5 diseases indicated by the average similarity to 20 cases for milk teeth growth phase of 80% and 30 cases for adult tooth growth phase of 90%.